2020
DOI: 10.1042/bsr20191043
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA files in the prevention of intestinal ischemia/reperfusion injury by hydrogen rich saline

Abstract: Background: Hydrogen-rich saline (HRS) has been proven effective against ischemia/reperfusion (I/R) injury. However, knowledge on the underlying signaling events remain poor. Having recent highlight of microRNAs (miRNAs) in mediating intestinal I/R injury, we hypothesized that HRS may protect intestine against I/R injury by regulating miRNAs. Method: Mice were given intraperitoneal injection of saline or HRS once daily for five consecutive days before undergoing intestinal I/R that was induced by 60-min ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Wang et al interestingly discovered that cytotoxin-associated gene A cytotoxin, a virulence factor of Helicobacter pylori that augments the risk of gastric cancer, can be delivered into host cells by the H 2 -utilizing respiratory chain of the bacterium, extending the roles of H 2 oxidation to include transport of a carcinogenic toxin [ 124 ]. Although this study indicated that H 2 may play a role in increasing gastric cancer risk, abundant studies also demonstrated that H 2 is protective in gastric damage induced by oxidative stress [ 125 ] and aspirin [ 126 ].…”
Section: Preventive and Therapeutic Applications Of H 2 mentioning
confidence: 99%
“…Wang et al interestingly discovered that cytotoxin-associated gene A cytotoxin, a virulence factor of Helicobacter pylori that augments the risk of gastric cancer, can be delivered into host cells by the H 2 -utilizing respiratory chain of the bacterium, extending the roles of H 2 oxidation to include transport of a carcinogenic toxin [ 124 ]. Although this study indicated that H 2 may play a role in increasing gastric cancer risk, abundant studies also demonstrated that H 2 is protective in gastric damage induced by oxidative stress [ 125 ] and aspirin [ 126 ].…”
Section: Preventive and Therapeutic Applications Of H 2 mentioning
confidence: 99%
“…Hydrogen, once thought to have no biological effects, has begun to receive widespread attention and research. It has been found that hydrogen plays an important protective role in multiple disease models and multiple clinical trials [37,38], especially in alleviating acute IRI in organs such as intestine [22,39,40], heart [41], liver and kidney [42]. These studies demonstrate that hydrogen can reduce IRI through antioxidant, anti-inflammatory, and other mechanisms.…”
Section: Discussionmentioning
confidence: 86%
“…MiR-23a-5p [27], miR-21 [29] miR-182 [34] and miR-199a-3p [35] upregulate while miR-29b-3p downregulates [30] in underlying II/R insult. Upregulation of miR-199a-3p dramatically decreased insulin-like growth factor-1, mTOR, and phosphoinositide-3-kinase regulatory subunit 1 protein expression as target genes of miR-199a-3p following II/R damage [35]. MiR-146a is a key regulator of the apoptosis of intestinal epithelial cells during I/R insult through TLR4/NF-ÎșB pathway [27].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs have been reported to be related to apotosis, in ammation, autophay, oxidative stress, and intestinal barrier dysfunction after IIR injury [26][27]. MiRNAs including miR-23a-5p, miR-146a, miR-21, miR-29b-3p, miR-381-p, miR-351-5p, miR-34a-5p, miR-665-3p, miR-682, miR-182 and miR-199a-3p have been involved in modulating mucosal damage following I/R damage in small intestines [27][28][29][30][31][32][33][34][35][36]. MiR-23a-5p [27], miR-21 [29] miR-182 [34] and miR-199a-3p [35] upregulate while miR-29b-3p downregulates [30] in underlying II/R insult.…”
Section: Discussionmentioning
confidence: 99%